Roland Barthes at the Collège de France - O'Meara, Lucy (Book collections on Project MUSE., 2012)
Roland Barthes at the Collg̈e de France studies the four lecture courses given by Barthes in Paris between 1977 and 1980. This study, the first full-length account of this material, places Barthes?s teaching within institutional, intellectual and personal contexts. Analysing the texts and recordings of Comment vivre ensemble, Le Neutre and La Prp̌aration du roman I et II in tandem with Barthes?s 1970s output, the book brings together for the first time all the strands of Barthes?s activity as writer, teacher and public intellectual. Theoretically wide-ranging in scope, Lucy O?Meara?s study focuses particularly on Barthes?s pedagogical style, addressing how his wilfully un-magisterial teaching links to the anti-systematic, anti-dogmatic goals of the rest of his work. Roland Barthes at the Collg̈e de France reassesses the critical and ethical priorities of Barthes?s work in the decade before his death, demonstrating the vitally affirmative core of Barthes?s late thought.